Archivists and Records Managers in the Information Age - Dollar, Charles M. (Archivaria, 1993)
In this article the author argues that the organization and use of electronically recorded information makes it imperative that archivists and records managers understand how their disciplines are engaged in a joint enterprise. In developing this argument, he reviews the common roots of archives and records management, examines the re-emergence of archives in North America in the 1940s and their subsequent divergence over the next three decades, and identifies the common ground that archives and records management share in dealing with electronically recorded information. This common ground, which includes records integrity, records disposition, and records accessibility over time, is linked into a single unifying theme by the importance of the contextual relations of electronic records. The article concludes with a call for archivists and records managers to participate in the design of metadata systems, in order to ensure that they contain the contextual information essential to a full understanding of records and records systems. RÉSUMÉ L'auteur de cet article soutient que l'organisation et l'utilisation de l'information consignée électroniquement rend impérative la nécessité pour les archivistes et les gestionnaires de documents de comprendre que leurs disciplines respectives sont désormais engagées dans une entreprise commune. L'auteur développe son argumentation en retraçant d'abord les sources communes de l'archivistique et de la gestion des documents; il examine ensuite la réapparition de l'archivistique en Amérique du Nord dans les années 1940 ainsi que leur divergence durant les trois décennies suivantes et identifie le territoire commun de l'archivistique et de la gestion des documents quant à l'information consignée électroniquement. Ce territoire commun (qui comprend l'intégrité des dossiers, la destruction et l'accès aux documents) est rattaché à un thème unique et unificateur par l'importance des relations contextuelles des archives électroniques. L'auteur conclut sur un appel lancé aux archivistes et aux gestionnaires de documents afin qu'ils collaborent à la conception des systèmes méta-informationnels afin de s'assurer que ces derniers contiennent l'information contextuelle nécessaire à un compréhension d'ensemble des dossiers et des systèmes de dossiers.